2017
DOI: 10.21873/anticanres.11821
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bevacizumab-induced Epithelial–Mesenchymal Transition by BATF2 Overexpression Involves the Suppression of Wnt/β-Catenin Signaling in Glioblastoma Cells

Abstract: Our findings expanded the understanding of the role of BATF2 in tumors, and also suggested a potential of using BATF2 as a therapeutic target to hinder bevacizumab induced EMT in glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…This hypothesis is supported by the gradual decrease in replicative activity among cancer cells in the present study, when the TGF-β1 concentration was reduced to 20 and 10 ng/ml. Other studies also support this hypothesis ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…This hypothesis is supported by the gradual decrease in replicative activity among cancer cells in the present study, when the TGF-β1 concentration was reduced to 20 and 10 ng/ml. Other studies also support this hypothesis ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 60%
“…However, as demonstrated in a previous study, cells of this line expressing the epitope prominin-1 (CD133) have high similarity of proteasomal profiles with neural CD133 + human stem cells and significant proteomic differences compared with normal mesenchymal stem cells of the human bone marrow ( 20 ). In a previous study ( 19 ), stimulation of U87 glioblastoma cells with TGF-β1 led to a significant increase in the expression of proteins associated with EMT, which markedly increased their invasiveness. These arguments served as the basis for choosing this line of tumor cells for studying the processes of cell-cell interaction in vitro .…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…EMT has been proven to be an important early event of tumor cell metastatic dissemination, in which cells are endowed with a more motile and invasive potential (41, 42). Previously, Huang W et al reported Bevacizumab induced EMT phenotype in glioblastoma cell line U87MG and the overexpression of BATF2 (basic leucine zipper ATF-like transcription factor 2), a multi-target transcriptional repressor, significantly inhibited Bevacizumab-induced EMT with suppression of Wnt/β-catenin signaling (43). In pancreatic cancer, Carbone et al established and validated two murine models of human pancreatic cancer resistant to Bevacizumab in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…However, these therapies exhibit certain disadvantages. For instance, bevacizumab, which is an inhibitor of the biological activity of vascular endothelial growth factor (VEGF) and is widely used in GBM treatment, stimulates EMT ( 56 , 57 ). This drawback is typical for tyrosine kinase inhibitors targeting tumor angiogenesis.…”
Section: Complex Therapy Of Glioblastoma and Csc Protein Targetsmentioning
confidence: 99%